The Impact of Social Media on Teachers' Teaching Creativity in Elementary Schools - Widiya Saputri Wulandari; Nurtanio Agus Purwanto; Agus Herwanto; Marwan Marwan (STAI Hubbulwathan Duri, 2025)
This study investigates the influence of social media usage on the teaching creativity of elementary school teachers. As digital platforms increasingly become part of educational practices, understanding their role in fostering teacher creativity is essential.A descriptive quantitative approach was employed, involving 76 teachers from SD Islam Al Azhar 31 Yogyakarta. Data were collected using a closed-ended questionnaire designed around validated indicators of social media usage and teaching creativity. The instrument was pilot-tested to ensure its validity and reliability. A One-Way ANOVA test was used to analyze the relationship between social media use and teaching creativity.The findings indicate that teachers frequently utilize social media as a source of inspiration and a collaborative platform, particularly for accessing visual media, planning interactive activities, and applying diverse teaching strategies. Reported engagement in creativity-related activities showed 30% of respondents indicating “always,” 25% “often,” and 20% “sometimes.” The ANOVA test revealed a significant relationship, with an F-value of 236.810 and a significance level of 0.001, indicating a strong positive correlation between social media use and teaching creativity.These results suggest that social media can effectively support the enhancement of teaching creativity by offering accessible resources and collaborative opportunities. However, the study is limited by its reliance on self-reported data and its focus on a single institution, which may affect the generalizability of the findings.This study highlights the potential of social media as a valuable tool in promoting professional creativity among teachers and serves as a reference for future teacher development programs.